Application of the Mathar method to identify internal stress variation in steel as a welding process result = Wykorzystanie metody Mathara do identyfikacji zmian naprężeń wewnętrznych w materiale stalowym po procesie spawania - Kowalski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper deals with the method to identify internal stresses in two-dimensional steel members. Steel members were investigated in the delivery stage and after assembly, by means of electric-arc welding. In order to perform the member assessment two methods to identify the stress variation were applied.
Keywords: internal stresses; residual stresses; post-welding stresses; post-welding creep; Barkhausen effect; tensometric measurement; semi-trepanation Mathar method; naprężenia własne; naprężenia pozostające; naprężenia pospawalnicze; skurcz spawalniczy; efekt Barkhausena; pomiar tensometryczny; metoda Mathara